Inflammatory Profiles and Glycemic Status in Type 2 Diabetes: Correlational Analysis of HbA1c, Leukocytes, and NLR - Mely Purnadian; Arshy Prodyanatasari (International Journal Of Health Science, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia due to impaired insulin secretion or action. Prolonged hyperglycemia elevates HbA1c levels, which may compromise leukocyte phagocytic function, leading to increased infection and inflammation risk. Leukocytosis has been linked to atherosclerosis and metabolic syndrome in T2DM, and an elevated neutrophil-to-lymphocyte ratio (NLR) is also associated with metabolic syndrome.Objective: This study aimed to investigate the correlation between HbA1c levels, leukocyte count, and NLR values in patients with T2DM at Kilisuci Hospital, Kediri City.Methods: A cross-sectional design was employed. Thirty T2DM outpatients from the Internal Medicine Polyclinic at Kilisuci Hospital were recruited via purposive sampling between March 17 and April 15, 2025, based on inclusion and exclusion criteria. HbA1c level served as the independent variable, while leukocyte count and NLR value were dependent variables. Data were analyzed using Kendall’s tau-b correlation test.Results: No significant correlations were observed between HbA1c levels and leukocyte count (p = 0.858) or between HbA1c levels and NLR values (p = 0.830). However, a significant positive correlation was found between leukocyte count and NLR values (p = 0.000), with moderate strength (τ = 0.480).Conclusion: HbA1c levels do not correlate with leukocyte count or NLR values in T2DM patients. Nevertheless, a significant correlation exists between leukocyte count and NLR. Future research should include larger sample sizes, incorporate secondary data alongside primary data, and compare NLR with other inflammatory markers.